First record of the jumping spider genus Bavia Simon, 1877 from India, with the description of a new species - Malamel, Jobi J.; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2015)
The tropical jumping spider genus Bavia was erected by Simon (1877) to include only the type species B. aericeps Simon, 1877, a relatively large, foliage-dwelling, plurident spider with broad carapace, long, tubular abdomen and longest and robust legs I (Murphy & Murphy 2000). To date, twenty species have been catalogued from Southeast Asia, Australia and Madagascar, of which six are known only from males, five only from females and nine are known from both sexes (World Spider Catalog 2015).